2017
DOI: 10.24926/iip.v8i2.519
|View full text |Cite
|
Sign up to set email alerts
|

The Imaginary Worlds of ISPOR: Modeled Cost-Effectiveness Claims Published in Value in Health from January 2016 to December 2016

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Over the past 30 years, literally thousands of imaginary modeled claims have been presented in the literature, including leading health technology assessment journals. Annual reviews of the status of cost-effectiveness or modeled claims in the three journals, Pharmacoeconomics , Value in Health and the Journal of Medical Economics found that the majority of models presented non-evaluable claims (typically lifetime cost-per-QALY) 37 , 38 , 39 , 40 , 41 . Where models were funded by a manufacturer a high proportion supported, in their modeled cost-per-QALY assessment, the manufacturer’s product.…”
Section: The Icer Reference Casementioning
confidence: 99%
“…Over the past 30 years, literally thousands of imaginary modeled claims have been presented in the literature, including leading health technology assessment journals. Annual reviews of the status of cost-effectiveness or modeled claims in the three journals, Pharmacoeconomics , Value in Health and the Journal of Medical Economics found that the majority of models presented non-evaluable claims (typically lifetime cost-per-QALY) 37 , 38 , 39 , 40 , 41 . Where models were funded by a manufacturer a high proportion supported, in their modeled cost-per-QALY assessment, the manufacturer’s product.…”
Section: The Icer Reference Casementioning
confidence: 99%
“…Over the past 30 years, literally thousands of modeled claims have been presented in the literature, including leading health technology assessment journals. Annual reviews of the status of cost-effectiveness or modeled claims in the three journals, Pharmacoeconomics , Value in Health and the Journal of Medical Economics found that the majority of models presented non-evaluable claims (typically lifetime cost-per-QALY) 20 , 21 , 22 , 23 , 24 . Where models were funded by a manufacturer a high proportion supported, in their modeled cost-per-QALY assessment, the manufacturer’s product.…”
Section: The Icer Reference Casementioning
confidence: 99%
“…Over the past 30 years, literally thousands of modeled claims have been presented in the literature, including leading health technology assessment journals. Annual reviews of the status of cost-effectiveness or modeled claims in the three journals, Pharmacoeconomics , Value in Health and the Journal of Medical Economics found that the majority of models presented non-evaluable claims (typically lifetime cost-per-QALY) 18 , 19 , 20 , 21 , 22 . Where models were funded by a manufacturer a high proportion supported, in their modeled cost-per-QALY assessment, the manufacturer’s product.…”
Section: The Icer Reference Casementioning
confidence: 99%